Javanese-Arabic Social Harmonization In The Development Of The Pekalongan Grand Mosque Architecture 1852-1933 - Wahyu Hadi Maulana; Soraya Adnani; Ahmad Anas Fajarul (Program Studi Sejarah Peradaban Islam Institut Agama Islam Darullughah Wadda'wah, 2026)
The dynamics of cultural interaction along the northern coast of Java in the 19th to early 20th centuries, particularly in the region of Pekalongan, created an intensive meeting space between Jsavanese and Arab communities that shaped a distinctive socio-religious structure. This harmony was reflected in religious practices, trade networks, and the architectural development of the Grand Mosque of Pekalongan from 1852 to 1933. This research aims to answer how the process of Javanese-Arab cultural acculturation occurred and how social harmonization was reflected in the architectural development of the Grand Mosque of Pekalongan. The historical method was employed through the stages of heuristics, source criticism, interpretation, and historiography, supported by literature studies and interviews. The analysis is based on theories of acculturation, material culture, and cultural agency to interpret architectural changes as representations of social practices and identity negotiation. The findings indicate that the Grand Mosque of Pekalongan is the oldest and largest mosque in the Pekalongan region. It was established in 1852 by the Regent of Pekalongan, Raden Ario Wiryo Tumenggung Adinegoro. In its early period, the mosque displayed a distinctly Javanese architectural style, reflected in its layout within the governmental center of Pekalongan based on the philosophy of Catur Gatra Tunggal, as well as in its structural form representing traditional Javanese architecture. Over time, the Grand Mosque of Pekalongan underwent architectural transformations characterized by the acculturation of Javanese and Arab elements. This acculturation process occurred as a result of intense social interaction and external cultural influences, particularly from the Arab community in Pekalongan. The outcome of this Javanese-Arab acculturation positioned the Grand Mosque of Pekalongan not only as a center of worship but also as a symbol of social harmony within the surrounding community.